THE IMPACT OF CHANGING CONSUMER BEHAVIOR ON THE MARKETING COMMUNICATION POLICY OF SPORTS AND ENTERTAINMENT COMPLEXES - IVANECHKO, NELIA; OKONSKYI, MYKHAILO (Herald of Khmelnytskyi National University. Economic sciences, 2025)
This article investigates the impact of evolving consumer behavior in the sports and entertainment services sector on the development and implementation of marketing communication policies for sports complexes. The study analyzes key changes in consumer preferences, motivations, and interaction methods with sports facilities, as well as their influence on the selection and effectiveness of communication tools. Particular attention is given to adapting the marketing communication policies of sports complexes to the new realities of the consumer market, including the use of digital technologies, personalized offers, and interactive forms of engagement with target audiences. The analysis reveals distinct characteristics across generations. Generation X  is characterized by thorough product research, a preference for an optimal balance of quality and price, high brand loyalty post-positive experience, and reliance on recommendations and independent information sources. Their media consumption includes traditional channels and select digital platforms. Millennials actively utilize mobile devices, prioritizing investment in experiences and personalized services. They are conscious consumers who value brands' social responsibility, are skeptical of traditional advertising, and instead trust recommendations and online reviews. Their key channels include online spaces, social media, high-quality websites, mobile applications, and blogs. Zoomers  are fully integrated into the digital ecosystem, interacting with brands primarily via smartphones. They value authenticity, innovation, and social responsibility, relying on peer recommendations, micro-influencers, and user-generated content. Their media consumption is dominated by short, dynamic, and visually rich video formats.  The findings provide recommendations for enhancing the effectiveness of marketing communication for sports and entertainment businesses amidst dynamic shifts in consumer behavior.
Keywords: consumer behavior; marketing communications; advertising; sports and entertainment services